Online marketing promotion of local tourism organizations: the analysis of the situation in Moravica administrative district - Garabinović, Dušan (Hotel and Tourism Management, 2019)
Modern information and communication technologies, especially the Internet, have caused many changes that influenced further development of the society, economy and tourism as their integrative part, and will do so in the future. Communication, that is the basis of every promotion, becomes more virtual, digital, online, but its purpose remains the same. Nowadays, even the tourist offer based on highly traditional values should be promoted in a modern way. The institutions of tourism at regional and local levels are much “closer” to the specific product, and such closeness enables better knowledge and understanding. Modern trends in tourism promotion enable local products to reach world proportions and be represented globally. The aim of this paper is to determine the Internet promotion orientation of local tourism organizations from the Moravica administrative district, examine their presence on the Internet in terms of having the official website and social network accounts, and make a comparison between them.